The coastal grasslands of the Eastern Cape west of the Kei River - Judd, Rachel Anne (Rhodes University, Faculty of Science, Botany Department, 1999)
The grasslands of South Africa are the foundation of commercial and subsistence agriculture yet they are being degraded at an alanning rate. The coastal grasslands of the Eastern Cape are no exception and they suffer added pressure of coastal resort development because of their proximity to an attractive coastline. In order to determine the degree of conservation necessary for any area it is essential to know what species occur there in order to determine if protection from habitat destruction is required. Four aims were defined for this studv. The initial aim was a phytogeographical classification of the grasslands in the coastal region west of the Kei River. This was done by vegetation sampling followed by computer based analysis with TWINSPAN. This analysis defined ten grassland associations. five being located in the area west of the Keiskamma River and five occurring east of it. The associations in the eastern half are termed mesic while those in the western balf are xeric. The second aim was to determine the presence of any underlying ecological gradients affecting the distribution of tbe associations. Indirect gradient analysis was carried out where samples are analysed irrespective of environmental factors. Direct gradient analysis was then carried out using scores per sample of various environmental factors. Environmental factors whicb migbt produce such gradients are both naturally-ocurring and man-induced. Natural factors which were recorded in the field include depth of soil at sample site, soil family, aspect and distance from the shore. An important factor is the land / sea interface. Natural factors analysed in the laboratory include soil pH. conductivity. percent organic matter, calcium, magnesium, phosphate and potassium. Man-induced factors are land use history e.g. Ploughing and grazing. Both direct and indirect gradient analysis were carried out with the computer based programme CANOCO. The third aim of the study was to determine the presence of any successional trends between the ten defined associations. This was done using several characteristics of the associations. Alpha and beta diversity were the first factors compared between associations. The percentage contribution of the Cyperaceae, Fabaceae, Asteraceae and Poaceae to each association was assessed and compared. The presence of various life forms of the species occurring in each association was determined together with the cover abundance of different classes of grass species. These results were then combined and analysed in the light of the results from CANOCO analvsis. They show that the mesic Themeda Iriandra - Anthospermum herhoceum, association which occurs closest to the shore and with the least disturbance is a depauperate form of the mesic climax Themeda triandra association. The mesic Hyparrhenia hirta - Dtheteropogon amplectens association may be a secondary grassland on account of phosphate and potassiun poor soils and land-use. The mesic Hyparrhenia hirta - Themedo triandra association is a slightly degraded form of the climax association due to grazing. The severely disturbed Stenotaphrum secundatum - C'entella coriacea association, which is located close to the shore, is a secondary grassland. Analysis of the xeric associations indicates a clearly defined ordination of associations on the basis of land-use. The Cynodon daclylon - Helictolrichon hirtulum and Sporobolis africanus - Setaria sphacelata associations which occur where ploughed lands have been left to lie fallow are secondary in nature. The Themeda triandra - Ehrharta calycina association is thought to be the closest representati ve of a climax xeric association but the presence of E. calycina indicates that some disturbance has occurred. The vegetation is subject to moderate grazing. The Cynodon dactylon - Ehrharla calycina and Diheleropogon filifolius - Ehrharla calycina associations are subject to varying intensities of trampling and grazing and are degraded forms of the Themeda triandra - Ehrharla calycina association. Because of tbe overriding influence of the land-use gradient separation along gradients of the remaining eight factors was limited. The effect of fire and temporal change in the mesic Themeda triandra and Hyparrhenia hirta - Themeeia trianda associations was assessed via long-term studies at Potter's Pass outside East London. The results show a quick response to burning with a return to 100% cover within six months by both associations. During spring the two associations could not be separated by either TWINSPAN or DECORANA. indicating a temporal shift from the Hyparrhenia hirta - Themeda triandra association to the Themeda triandra association. The fourth and final aim was to identify plants requiring protection from habitat destruction and to make recommendations for further conservation areas and management of the coastal grasslands. Through the collection and identification of as many plants as possible a species checklist was prepared and the status of each was determined through reference to the Red Data Book of threatened and endangered species. Kniphofia rooperi is vulnerable in the Cape and Euphorbia hupleuroides is considered rare in kwazulu-Natal. Ten species are endemic to the Cape and / or South Africa. The richness of the vegetation lies in the presence of species representative of the four major floras which converge in the eastern Cape. i.e. The Cape, NamaKarroo, Tongoland-Pondolaod floras and the Kalahari Highveld Regional Transitional Zone. Suggestions are made for the conservation of the grassland associations at various sites within the study area based on the present area conserved. Less than 2% of the coastline in the study area is conserved and it is felt that the area under conservation should be increased. Management suggestions based on the available literature are given for both farmed and conserved areas. There is a great potential for further studies on grassland dmamics within the areas surveyed. In terms of management, the grasslands require careful examination to determine the most effective season in which to burn if at all. As with most agricultural systems in South Africa. grazing strategies will benefit from further research. Any additional research on the dynamics of these grasslands can only be of benefit to the sustained utilisation of this vital resource.
Keywords: Grassland ecology -- South Africa -- Eastern Cape; Grasslands -- South Africa -- Eastern Cape